UNDERSTANDING CUSTOMER LOYALTY IN INDONESIA QUICK SERVICE RESTAURANT INDUSTRY - Juliana Juliana; Amelda Pramezwary; Dhana Calista Oktaviani; Felicia Tania E; Michelle A. Benly (Indonesian Marketing Journal, 2021)
In the restaurant industry, customer loyalty has become the most important strategic goal. The impact of service quality dimensions on customer loyalty is investigated using the SERVQUAL scale's dimensional structure in fast food restaurant service environments. Pizza Hut is a well-known fast-food chain that appeals to people of all ages, from children to the elderly. Pizza Hut has locations throughout the city as well as internationally. Each branch's level of service is unquestionably different. Pizza Hut Indonesia will be the subject of this study. A sample of 100 respondents is used to create and test research hypotheses. Quantitative research is the form of research that we used in this study. A questionnaire was used to collect data from everyone who has ever visited Pizza Hut Indonesia. PLS-SEM was utilized to perform the data analysis. According to the data, total consumer loyalty is 44,8 percent. As a consequence of this research, consumer loyalty at Pizza Hut Indonesia is substantially influenced by service quality.